The tragic destiny of a mining camp: Morococha - Bonilla Mayta, Heraclio (2020)
This article reviews the tragic trajectory of Morococha mining site, through a historical exploration of the formation process of the mining complex. Likewise, it describes the living conditions of its population that remained trapped between an old Morococha city in ruins and the new Morococha, turned into a ghost town. It is, therefore, as the chronicle of a death foretold, that is reproduced over and over again in various contexts of the national space, such as the destiny or the fate of every mining center. This situation is reflected in the current days, due to people who manage economic policies, and assume that the prosperity of one country lies in the efficient exploitation of its comparative advantages, based on the exploitation of its minerals.